2008
DOI: 10.1111/j.1447-073x.2007.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Zygomaticofacial, zygomaticoorbital and zygomaticotemporal foramina: Anatomical study

Abstract: The zygomatic nerve may be disrupted when elevating periorbita from the lateral wall during orbital surgery, and care should be taken to prevent injury to this nerve during lateral orbitotomy approaches to access intraorbital soft-tissue tumors. Furthermore, the precise introduction of anesthetics to the zygomaticoorbital (ZO), zygomaticofacial (ZF) and zygomaticotemporal (ZT) foramina could be important data for the plastic and reconstructive surgeon operating in the area. The aim of the present study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 16 publications
3
32
1
Order By: Relevance
“…The absence of the ZMF has been reported to be 9.1% in Koreans (Hwang et al, 2007), 21.8% in Indians (Mangal et al, 2004), 21.5% in Caucasians (Martins et al, 2003), and 39% in a mixed cohort, chiefly Caucasians (Loukas et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The absence of the ZMF has been reported to be 9.1% in Koreans (Hwang et al, 2007), 21.8% in Indians (Mangal et al, 2004), 21.5% in Caucasians (Martins et al, 2003), and 39% in a mixed cohort, chiefly Caucasians (Loukas et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Some authors have suggested that the zygomatico-facial (ZMF) may be used as a landmark for locating the IOF (Chanda and Nanda, 2002;Gonzales et al, 2002;Martins et al, 2003). Although there are many studies regarding the incidence and number of the ZMF in literature (Mangal et al, 2004;Loukas et al, 2008), only a few of them have presented the pertinent metrical data for finding the IOF (Martins et al, 2003). It was the purpose of this study to collect the morphometric details of the relevant parameters and to determine the reliability of the ZMF for locating the lateral end of the IOF.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, we released a very similar exploration of the zygomaticofacial, zygomaticoorbital, and zygomaticotemporal foramina (Loukas et al, 2008). We congratulate their efforts in conveying how surgeons operating in this area should possess knowledge of the prevalence of the zygomaticofacial foramen with respect to its utilization as a landmark.…”
Section: To the Editor Clinical Anatomymentioning
confidence: 94%
“…There were none in 15.6%, one in 44.4%, two in 28.1%, three in 6.3%, four in 4.4%, and five in 1.3% of sides. Loukas et al (2008) studied 200 dry human skulls for zygomaticofacial (ZF), zygomaticoorbital (ZO) and zygomaticotemporal (ZT) foramina. All three foramina varied from absence to as many as four small openings.…”
Section: Zygomatic Bonementioning
confidence: 99%